New oral anthelmintic intraruminal delivery device for cattle - Thierry F Vandamme (Wolters Kluwer Medknow Publications, 2014)
Background: The purpose of this work was to develop a new oral drug delivery system intended for cattle and that enables delayed and pulsed release of an anthelmintic agent. Materials: This new tailored dosage form, also called reticulo-rumen device (RRD) has been evaluated on grazing calves by means of measurements of milliunits of tyrosine concentration, number of eggs per gram of feces, mean number of infective larvae on cattle pasture and increase in mean weight of cattle. Methods: The in vivo evaluation was carried out during two grazing seasons on different groups of dairy cattle. During the first grazing season, Group 1 was designated as an untreated control group. The remaining two were assigned to different treatments as follows: Group 2, early season suppression with a marketed intraruminal slow release bolus (Chronomintic ® , Virbac) administered immediately prior to turn-out and Group 3, mid-season suppression with a new RRD administered immediately prior to turn out. When the cattle were turned out at the start of the second grazing season, they were not given any anthelmintic treatment and were divided into two different groups, corresponding to the previous groups that received an anthelmintic treatment during the first grazing season, on that pasture that they had occupied as separate groups in the previous year. Furthermore, during the second season, samples of feces, blood and herbage were collected every month. Results and Conclusion: During the first grazing season, the results indicated that the fecal egg counts and the number of infective larvae in herbage samples were slightly lower for the group receiving the new RRDs. Regular weighing of the cattle receiving the new RRDs revealed no significant difference with cattle receiving marketed RRDs. Conversely, during the second grazing season, the results for the mean weights of the cattle demonstrated that the weights of animals having been administered new RRDs during the first grazing season were significantly different (P < 0.05) from those in the second group treated with a Chronomintic ® during the first grazing season. A difference in mean weight of 26 kg was observed between these two groups.